The Role of Mother Knowledge and Parenting Culture in Determining the Toddler Nutrition Status - Kadir, Sunarto (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2019)
Background: A good nutritional status can be a foundation of child health that can optimize growth and development of young children and reduce morbidity, disability, and death. it also will improve the quality of human resources. Gorontalo Province was in the third position with the number of toddler with malnutrition status 7.8% in 2018 after the Maluku provinces and East Nusa Tenggara provinces. In addition, Gorontalo province also occupies the fourth highest position with the number of toddlers with nutritional overweight status of 4.7% after Papua and DKI Jakarta. Therefore, the aim of research is to analyze the contribution of knowledge about parenting, and cultural parenting to the toddler’s nutritional status.Methods: The research employed a cross sectional study and involved 50 toddlers in the site area as the sample by using the total sampling technique. Moreover, the data were analyzed by the chi-square.Result: The results showed that there was no relationship between knowledge about parenting and the nutritional status of toddler with a P value of 0.062> α 0.05 and there was a relationship between the cultural parenting with the nutritional status of toddler with P Value 0.013 <α 0.05.Conclusion : The Health community center should to optimize nutritional programs that are supported a positive deviating increasing nutritional status and positive motivation changing parenting culture patterns that give a negative impact to toddler nutritional status.